2006
DOI: 10.1007/s10657-006-5671-4
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and contracts: Franchising

Abstract: Franchising, Institutions, Contracts, Legal systems,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
0
9
0
5
Order By: Relevance
“…As Dant et al (2008) recently showed, the proportion of company-owned outlets is almost three times greater in France than in the United States. A potential explanation is that civil law countries such as France regulate dispute resolution more heavily than common law countries such as the United States (Pfister et al, 2006). Thus, greater reliance on company ownership may be a way for French chain operators to avoid potentially long and costly disputes with franchisees.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…As Dant et al (2008) recently showed, the proportion of company-owned outlets is almost three times greater in France than in the United States. A potential explanation is that civil law countries such as France regulate dispute resolution more heavily than common law countries such as the United States (Pfister et al, 2006). Thus, greater reliance on company ownership may be a way for French chain operators to avoid potentially long and costly disputes with franchisees.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…A recent study by Pfister et al (2004) demonstrated the implications of variance in legal traditions, labor regulations, and trademark protection across countries for the organization of franchise channels. It may thus well be that, across countries, the need for institutional solutions to protect franchisees falls apart and/or that differences in the legal status of such arrangements makes them more powerful in some countries than in others.…”
Section: Limitationsmentioning
confidence: 99%
“…Clearly, the franchisor can only offer financing to his franchisees, if he has access to capital. Hence, franchisor financing is used as an additional indicator for the franchisor's access to capital (see, e.g., Lafontaine 1992;Pfister et al 2006). Minimum investment is the minimum amount the franchisee is required to invest when starting his business.…”
Section: Independent Variables Concerning Franchisor's Capital Scarcitymentioning
confidence: 99%
“…However, empirical results often suggest the opposite. Other researchers (Pfister et al 2006) predict a larger proportion franchised for older franchise systems, because franchisors expand their business by means of franchising or find it easier to franchise due to reduced costs and obstacles. For example, a business with a long tradition might signal good reputation and quality to potential franchisees.…”
Section: Control Variablesmentioning
confidence: 99%